Analog precoder and equalizer design for multichannel communication - Fan, Z.; Scharf, L.; Gubner, J.A. (2004 IEEE 5th Workshop on Signal Processing Advances in Wireless Communications : Lisbon, Portugal, 11-14 July, 2004, 2004)
This work addresses joint analog precoder and equalizer design for multichannel data transmission over the frequency-selective additive Gaussian noise (AGN) channel. The design goal is to maximize mutual information rate subject to a transmit power constraint. We assume a continuous channel model with precoder transmissions for M subchannels that lie in an n dimensional linear subspace of L/sup 2/(R). We first design the subspace according to the channel characteristics, and then design the precoders as functions in this subspace.